Concussion management knowledge among residents and students and how to improve it. (3rd August 2017) - Haider, Mohammad N; Leddy, John J; Baker, John G; Kiel, John M; Tiso, Michael; Ziermann, Karl A; Willer, Barry S
Aim: Recognition and management of concussion is an area of growing importance. The objective was to measure concussion knowledge among residents and medical students (MS).Methods: Baseline knowledge was assessed by a standardized questionnaire. Control group (family medicine [FM], pediatric medicine [PM] and emergency medicine) residents were given reading material, and intervention group rotated in a clinic (sports medicine residents and MS). Subjects were retested after 36.82 (16.1) days. Pre- and post-intervention test scores were compared.Results: The average baseline knowledge scores were 79.2% for emergency medicine residents, 61.4% for FM, 68.5% for PM, 71.7% for sports medicine residents and 68.0% for MS. Knowledge increase for control group was 1.16% compared with 14.41% for the clinical rotation group (p < 0.0001).Conclusion: PM and FM residents can benefit from more focused education about concussion.